NLRP7 and the Genetics of Hydatidiform Moles: Recent Advances and New Challenges - Slim, Rima; Wallace, Evan P. (Frontiers in Immunology, 2013)
NOD-like receptor proteins (NLRPs) are emerging key players in several inflammatory pathways in Mammals. The first identified gene coding for proteins from this family is Nlrp5 and was originally called Mater for “Maternal Antigen That mouse Embryos Require” for normal development beyond the 2-cell stage. This important discovery was followed by the identification of other NLRPs playing roles in inflammatory disorders and of the first maternal-effect gene in humans, NLRP7, which is responsible for an aberrant form of human pregnancy called hydatidiform mole (HM). In this review, we recapitulate the various aspects of the pathology of HM, highlight recent advances regarding NLRP7 and its role in HM and related forms of reproductive losses, and expand our discussion to other NLRPs with a special emphasis on those with known roles in mammalian reproduction. Our aim is to facilitate the genetic complexity of recurrent fetal loss in humans and encourage interdisciplinary collaborations in the fields of NLRPs and reproductive loss.